Effects of metformin on endometrial cancer cell growth in vivo: A preoperative prospective trial. Issue 19 (10th June 2014) - Mitsuhashi, Akira; Kiyokawa, Takako; Sato, Yasunori; Shozu, Makio
Abstract : BACKGROUND: Metformin, an antidiabetic drug, decreases the incidence of various cancers in diabetic patients. Metformin‐induced inhibition of cancer cell proliferation has been confirmed in vitro but not in humans. Because endometrial cancer is associated with insulin resistance, the authors investigated whether a diabetes‐therapeutic metformin dose inhibits cancer cell growth in patients with endometrial cancer. METHODS: A dose of metaformin was administered (1500‐2250 mg/day) to 31 patients with endometrial cancer preoperatively for 4 to 6 weeks. Cell proliferation was assessed in patient tissues using immunohistochemical and Western blot analyses and DNA synthesis was measured in serum using a thymidine uptake assay. All statistical tests were 2‐sided. P values of < .05 were considered statistically significant. RESULTS: Preoperative metformin treatment decreased DNA synthesis in sera and significantly reduced the Ki‐67 (mean proportional decrease, 44.2%; 95% confidence interval [95% CI], 35.4‐53.0 [ P < .001]) and topoisomerase IIα (mean proportional decrease, 36.4%; 95% CI, 26.7‐46.0 [ P < .001]) labeling indices. Levels of phospho‐ribosomal protein S6 and phospho‐extracellular signal‐regulated kinase 1/2 (ERK1/2) were found to be significantly decreased and phospho‐adenosine monophosphate‐activated protein kinase and p27 levels were significantly increased. Preoperative metformin use caused significant decreases in circulating factors, including insulin, glucose, insulin‐like growth factor 1, and leptin. DNA synthesis‐stimulating activity in patient sera was significantly decreased during metformin administration. CONCLUSIONS: An antidiabetic dose of metformin inhibited endometrial cancer cell growth in vivo, an effect likely due to its effect on humoral factor(s). This translational study provides considerable rationale to initiate large clinical trials. Cancer 2014;120:2986–2995. © American Cancer Society . Abstract : The results of the current study demonstrated that an antidiabetic dose of metformin inhibits endometrial cancer cell growth in vivo. Preoperative metformin use caused significant decreases in circulating humoral factors in patients with endometrial cancer.